Prosperity Far Distant : The Journal of an American Farmer, 1933-1934 - Wiltse, Charles M. (Charles Maurice), 1907-1990 (Book collections on Project MUSE., 2012)
Fresh from receiving a doctorate from Cornell University in 1933, but unable to find work, Charles M. Wiltse joined his parents on the small farm they had recently purchased in southern Ohio. There, the Wiltses scratched out a living selling eggs, corn, and other farm goods at prices that were barely enough to keep the farm intact. In wry and often affecting prose, Wiltse recorded a year in the life of this quintessentially American place during the Great Depression. He describes the family's daily routine, occasional light moments, and their ongoing frustrations, small and large-from a neig.